If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (A + -3) * X = 5 Reorder the terms: (-3 + A) * X = 5 Reorder the terms for easier multiplication: X(-3 + A) = 5 (-3 * X + A * X) = 5 Reorder the terms: (AX + -3X) = 5 (AX + -3X) = 5 Solving AX + -3X = 5 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '3X' to each side of the equation. AX + -3X + 3X = 5 + 3X Combine like terms: -3X + 3X = 0 AX + 0 = 5 + 3X AX = 5 + 3X Divide each side by 'X'. A = 5X-1 + 3 Simplifying A = 5X-1 + 3 Reorder the terms: A = 3 + 5X-1
| -16+m=0 | | 22-3x=7 | | 4x-8x=52 | | 4t-2=2t+15 | | 9g=3+(-4+5g) | | 3(u+1)=7u+11 | | a/4-8=10 | | 3xy-2y=2x+3 | | 4(w+6)-7w=12 | | 4x-11=-54-9x | | 5x+2(4+x)=9 | | 8h-17=36 | | 4+(3x+7)+5=33 | | P-17=-21 | | t^5-4=10 | | -4(-5v-3)=92 | | 3y-12=8 | | 1/4=log16(17-5n) | | 86=6x+6 | | -7x+2x=-100 | | x^2+18+63=0 | | a^3+6=12 | | 16+-16+-6+6= | | 2(x+2)2(x+2)-3=3 | | t^3-6=13 | | 2x-6x=12+2x | | a^6+2=16 | | 6*j+j=700 | | 6j+j=700 | | Q=10-ln(x) | | 8x+2=3(x+4) | | 7x-4-3x=15-2x-1 |